Production of Laccase by Cochliobolus sp. Isolated from Plastic Dumped Soils and Their Ability to Degrade Low Molecular Weight PVC - Tirupati Sumathi; Buddolla Viswanath; Akula Sri Lakshmi; D. V. R. SaiGopal (Biochemistry Research International)
One of the utmost man-made problems faced today has been the ever-increasing plastic waste filling the world. It accounts for an estimated 20–30% (by volume) of municipal solid waste in landfill sites worldwide. Research on plastic biodegradation has been steadily growing over the past four decades. Several fungi have been identified that produce enzymes capable of plastic degradation in various laboratory conditions. This paper presents a study that determined the ability of fungi to degrade low molecular weight polyvinyl chloride (PVC) by the enzyme laccase. We have isolated a fungal species, Cochliobolus sp., from plastic dumped soils and they were cultured on Czapek Dox Agar slants at 30°C. The effectiveness of this fungal species on the degradation of commercial low molecular weight polyvinyl chloride (PVC) was studied under laboratory conditions. Significant differences were observed from the FTIR, GC-MS, and SEM results in between control and Cochliobolus sp. treated PVC.